2018
DOI: 10.1111/sltb.12456
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Religion Associated with Suicide Attempt and Suicide Ideation in Depressed, Religiously Affiliated Patients

Abstract: There is substantial evidence to support the claim that religion can protect against suicide ideation, suicide attempts, and completed suicide. There is also evidence that religion does not always protect against suicidality. More insight is needed into the relationship between suicidal parameters and dimensions of religion. A total of 155 in- and outpatients with major depression from a Christian Mental Health Care institution were included. The following religious factors were assessed: religious service att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 60 publications
0
15
0
2
Order By: Relevance
“…Nevertheless, it has been demonstrated that religiosity, either as broad participation or through a religious association, was associated with protection against suicide proportional to the degree of participation in religious activities [25]. Jongkind et al [46] demonstrated that higher moral objections to suicide (MOS) and a positive-supportive God representation in Catholic patients with MDD were negatively correlated with suicide ideation. This may be putatively true for our sample which consists of Catholics, but we did not assess the degree of participation in religious activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it has been demonstrated that religiosity, either as broad participation or through a religious association, was associated with protection against suicide proportional to the degree of participation in religious activities [25]. Jongkind et al [46] demonstrated that higher moral objections to suicide (MOS) and a positive-supportive God representation in Catholic patients with MDD were negatively correlated with suicide ideation. This may be putatively true for our sample which consists of Catholics, but we did not assess the degree of participation in religious activities.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these evidences might be an indicator of an NRC [46]. Francis et al [47] found that NRC, rather than PRC, demonstrated a significant association with depressive and anxiety symptoms, but they evaluated 622 medical students (therefore a nonclinical sample).…”
Section: Introductionmentioning
confidence: 99%
“…Há indícios de que possuir uma prática religiosa se constitui como um importante fator protetivo em saúde e costuma atuar como uma estratégia de enfrentamento para uma série de condições clínicas, além de estar associada a bons índices de qualidade de vida, bem-estar e outros benefícios (Fleury et al, 2018). Embora os resultados deste trabalho tenham associado a religiosidade com a menor prevalência de comportamentos suicidas, vale dizer que esta hipótese ainda é inconsistente na literatura científica (Jongkind, Van den Brink, Schaap-Jonker, Van der Velde, & Braam, 2018). Inclusive, um estudo aponta que a religiosidade não é eficaz como fator protetivo à ideação suicida, apenas frente às tentativas e, possivelmente, ao suicídio consumado (Lawrence, Oquendo, & Stanley, 2016).…”
Section: Discussionunclassified
“…Similarly, religiousness also seems to protect individuals from suicide attempts (Lawrence et al 2016) in most major religious denominations (Gearing and Alonzo 2018;Stack and Kposowa 2011). In one recent study, there was a negative relationship between suicide ideation and attempts and dimensions of religion (e.g., moral objection of suicide), suggesting that religiousness plays a significant role in reducing suicide attempts and ideations (Jongkind et al 2019).…”
Section: Introduction: Religions and The Stigma Of Suicidementioning
confidence: 99%